Multi-omics analysis reveals that alginate oligosaccharides mitigate ochratoxin A-induced renal impairment in mice and is relevant to the regulation of PPAR signaling - Ye, Xueqing; Zhao, Yue; Yao, Qinghua; Zhang, Xu; Li, Sibing; Liu, Wenchao (Frontiers in Veterinary Science, 2026)
IntroductionOchratoxin A (OTA) is a core environmental toxin that induces kidney injury by interfering with glomerular filtration, antioxidant defense, and tubular transport functions. Alginate oligosaccharides (AOS), as active substances from marine, carry natural antioxidant, anti-inflammatory and other biological activities. The purpose of this study is to explore the molecular network of AOS against nephrotoxicity caused by OTA.MethodsA total of 36 5-week male mice were randomly divided into three groups: the CON group, the OTA group (250 μg/kg B.W. OTA) and the AOS + OTA group (400 mg/kg B.W. AOS +250 μg/kg B.W. OTA). The treatment was continued for 21 d.ResultsOTA induced renal injury in mice, manifested by glomerular capsule blurring, lymphocytic infiltration, and mitochondrial damage in tubular epithelial cells. Treatment with AOS significantly alleviated these pathological changes. Multi‑omics analysis revealed that AOS activated the PPAR signaling pathway, upregulating key genes (Aldehyde Dehydrogenase 1 Family Member A3 (Aldh1a3), Carbamoyl-phosphate synthase 1 (Cps1), Cytochrome c oxidase subunit 8B (Cox8b)), which drove the accumulation of protective metabolites such as L‑arginine and carnosine. This protective process involved coordinated regulation of amino acid metabolism, mTOR signaling, and PPAR pathways, illustrating a novel metabolic‑transcriptional network through which AOS mitigates OTA‑induced nephrotoxicity.DiscussionThis study reveal that AOS antagonizes OTA-induced nephrotoxicity in mice through PPAR signaling axis, thus providing new insight into the renal protection mechanism of marine active substances.